TINGKAT KEPATUHAN PENGGUNAAN MASKER DAN HAND SANITIZER MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 JAKARTA SELAMA PANDEMI COVID-19 - Kining, Ekajayanti; Ginting, Dina Marsella Br.; Sogandi, Sogandi (JURNAL MEDIA KESEHATAN, 2021)
Wearing mask and hand hygiene were the main choices in an effort to reduce the transmission of Covid-19 when doing outdoor activity. Various efforts have been made by the government in disseminating this recommendation to all levels of society including college students. College students as a layer with a high level of education were expected to obey the appeal given, including students of the University of 17 August 1945 Jakarta. This study aimed to determine the compliance college students at the University of 17 August 1945 of wearing mask and hand sanitizer during the Covid-19 pandemic. The method was used descriptive quantitative with a cross-sectional study design. Data collection used an online questionnaire containing closed questions. A total of 309 people participated in this survey and answered the use of masks and hand sanitizers. College students used masks and hand sanitizers during the Covid-19 pandemic. The compliance rate for the use of masks was 68.6% and hand sanitizer 78.3% during the Covid-19 pandemic. Men werw more obedient to using mask 73.6% and hand sanitizer 84.3% compared to women using mask 64.5% and hand sanitizer 73.4%.